Reconstruction of extensive abdominal wall defect using an eccentric perforator‐based pedicled anterolateral thigh flap: A case report. Issue 6 (9th July 2013) - Jang, Joonchul; Jeong, Seong‐Ho; Han, Seung‐Kyu; Kim, Woo‐Kyung
<x xml:space="preserve">Abstract</x> Reconstruction of extensive abdominal wall defects is a challenge for reconstructive surgeons. In this report, a case of reconstruction of a large abdominal wall defect using an eccentric perforator‐based pedicled anterolateral thigh (ALT) flap is presented. A 30‐year‐old man presented with recurrent desmoid‐type fibromatosis in the abdominal wall. The recurrent tumor was radically excised, and the en bloc excision resulted in a full‐thickness, large abdominal wall defect (25 cm × 20 cm). An eccentric perforator‐based pedicled ALT flap, including wide fascial extension, was transferred to the abdominal defect; fascial portions were sutured to the remnant abdominal fascia. Plication of the fascia along the sutured portion was performed to relieve the skin tension between the flap and the marginal skin of the abdominal defect. Eight months after surgery, the reconstructed abdomen had an acceptable esthetic appearance without tumor recurrence or hernia. The use of an eccentric perforator‐based pedicled ALT flap may be an alternative method for the reconstruction of extensive abdominal wall defects. © 2013 Wiley Periodicals, Inc. Microsurgery 33:482–486, 2013.